Analysis of Hospital Legal Responsibility in Cases of Refusal of Emergency Patients Based On Law No. 17 of 2023 Concerning Health - Naurah, Gladdays; Simarmata, Marice; Risdawati, Irsyam; Sumarno, Sumarno; Zarzani, Tengku Riza (LEGAL BRIEF, 2025)
Emergency services are stipulated in Law No. 17 of 2023 concerning Health, which stipulates that hospitals may not reject emergency patients for any reason. However, there are still cases of rejection of emergency patients that result in legal consequences for hospitals and health workers. This study aims to analyze the responsibility of hospitals in handling emergency patients based on applicable regulations reviewed from civil, criminal, and administrative law for cases of patient rejection. This study uses a normative juridical method with a statutory approach and relevant concrete cases. The analysis was carried out by referring to the provisions of Law No. 17 of 2023 concerning Health, the Regulation of the Minister of Health, and the Supreme Court Decision Number 68/G/TF/2019/PTUN-SRG and the case of patient rejection at Hermina Hospital Malang on March 11, 2024. The results of the study indicate that patient rejection by hospitals can result in serious legal consequences, including civil lawsuits, criminal sanctions, and administrative sanctions for the responsible parties. Based on these findings, it is necessary to strengthen the monitoring system, increase awareness of health workers, and comply with standard operating procedures to ensure that emergency services run optimally and in accordance with legal provisions.